The technician and the politician: About the publicized deactivation of the National Civil Service Authority in a VUCA environment - Huamán Ordóñez, Luis Alberto (2024)
This essay analyzes the dynamics of the technical and the political in the exercise of the activity of the National Civil Service Authority - SERVIR before the proposal of the Congress of the Republic to proceed to the repeal of Legislative Decree N.° 1023 that it is the structural support of the governing body. It identifies a first moment of an organization where liberal ideas seasoned with social conformism prevailed until reaching 1950 where it opted for a statutory regime, generating, in turn, the National Council of the Civil Service and then appearing, in a second moment, the Institute National Public Administration focused on the rationalization of the administration that in the fujimorato is dismantled with the purpose of implementing labor flexibility policies in the public sector and, in a third moment within a VUCA environment, the Authority appears that faces the COVID-19 promotes remote work, opening space for teleworking, as well as the conflicts generated by Law N.° 31131, as well as the internal problems with the union of the governing institution, the request for repeal of Legislative Decree N.° 1602 and the barometer of citizen perception is not always favorable. With the use of hermeneutic and historical techniques, he concludes that it is necessary for SERVIR to assume an institutional position based on a deliberative public administration focused on reconciling positions with the various interest groups with which it must relate for the benefit of citizens.